Balance Training in Modern Dancers Proprioceptive-Neuromuscular Training vs Kinesio Taping - AGOPYAN, ANİ (SCIENCE & MEDICINE INC, 2018)
Kinesio tape and proprioceptive exercises are both used for increasing balance in dancers. The purposes of this study were to: a) determine the acute effect of kinesio tape (KT) application on the ankle joint on balance performance, b) investigate the effects of an 8-week proprioceptive-neuromuscular (PN) training program on balance performance, and c) compare their effects vs modern dance technique classes alone. Thirty-three trained, university-level modern dance students (9 male, 24 female) were divided randomly into three groups: kinesio tape (KT, n=11), proprioceptive-neuromuscular (PN, n=11), or control (n=11). Static (turn-out passe-opened eyes/releve and turn-out passe-closed eyes/flat foot), semi-dynamic (airplane), and dynamic balance (monopodalic-straight and -transverse in a turn-out passe-eyes opened/flat foot) tests were performed before and after the intervention. One day after pre-tests, KT mechanical correction technique was applied to the left ankle joint (supporting leg) in the KT group, and tests were repeated to determine the acute effect of KT. The PN group participated in an 8-week balance training program (2 days/wk, 60 min/day) involving exercises using stable and unstable surfaces. Significant improvements were observed for all static and dynamic balance tests in the PN group; semi-dynamic airplane and dynamic monopodalic-straight and transverse tests improved in the KT group; and only semi-dynamic airplane test scores changed significantly for the control group (p<0.05). Our findings suggest that with the exception of the semi-dynamic airplane test, both PN training and KT application were more effective at improving balance performance for modern dancers than modern dance technique classes alone.
Keywords: BALLET DANCERS; STRENGTH; STABILITY; ANKLE; YOUNG; PERFORMANCE; BIOMECHANICS; INDIVIDUALS; QUADRICEPS; EXERCISE